Laser Engineering Net Shaping of Microporous Ti6Al4V Filters - Gualtieri, Thomas; Bandyopadhyay, Amit (Frontiers in Mechanical Engineering, 2016)
In many applications, porous metal structures are necessary for proper and optimal function. Yet, these structures can be difficult to build. It is especially difficult if the pore size desired is very fine or on the microscale. For this reason, additive manufacturing processes have been looked at to build these structures. In this study, Laser Engineering Net Shaping (LENS™) processing was experimented with processing interconnected microporous structures. Using Ti6Al4V and only changing processing parameters, porous structures were created having porosity ranging from 21.5 to 15.4%. The microstructure proved to be that of traditional laser processed Ti6Al4V parts. Compression test of these samples showed that the ultimate compressive strength varied from 645 to 556 MPa. Overall, LENS™ proved to be a viable method to make unique interconnected microporous structures that could be easily added to any build without having to change the design.